2016
DOI: 10.1038/srep26081
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of weak localization in quantum interference effects observed in epitaxial La0.7Sr0.3MnO3 ultrathin films

Abstract: Quantum interference effects (QIEs) dominate the appearance of low-temperature resistivity minimum in colossal magnetoresistance manganites. The T1/2 dependent resistivity under high magnetic field has been evidenced as electron-electron (e-e) interaction. However, the evidence of the other source of QIEs, weak localization (WL), still remains insufficient in manganites. Here we report on the direct experimental evidence of WL in QIEs observed in the single-crystal La0.7Sr0.3MnO3 (LSMO) ultrathin films deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 28 publications
4
38
0
Order By: Relevance
“…This is not consistent with the double exchange mechanism which couples the ferromagnetism to metallicity, as in bulk LSMO. Transport analysis shows that the anomalous FMI phase is due to the Anderson localization effect [39,57,71]. As shown in Figure 13, the temperature-dependent resistivity indicates that LSMO films on STO gradually evolve from weak localization to strong localization, with reducing thickness.…”
Section: Anderson Localization Effectmentioning
confidence: 91%
“…This is not consistent with the double exchange mechanism which couples the ferromagnetism to metallicity, as in bulk LSMO. Transport analysis shows that the anomalous FMI phase is due to the Anderson localization effect [39,57,71]. As shown in Figure 13, the temperature-dependent resistivity indicates that LSMO films on STO gradually evolve from weak localization to strong localization, with reducing thickness.…”
Section: Anderson Localization Effectmentioning
confidence: 91%
“…1 electron-electron (e-e) interaction could also become a dominant factor that affects the resistivity. The temperature-dependent resistivity correction due to e-e interaction can take the form of ~ / , where A 2 is a constant [30][31][32]. The electron-electron interaction combined with electron-phonon interaction could produce an upturn in the resistivity at low temperature, however, it is insensitive to external magnetic field and thus cannot be applied to our situation.…”
mentioning
confidence: 98%
“…These observations suggests a reinterpretation of some results suggesting weak localization at relatively high fields 35 , but not those observed at very low fields 28 .…”
Section: Electron-electron Interactions Explain the Majority Of The Rmentioning
confidence: 54%
“…In addition, in polycrystalline materials a resistivity minimum may also be due to antiferromagnetically aligned grains [18][19][20] . Previous reports concerning the resistivity minimum in magnetic oxides have shown that electron-electron interactions are by the far the most commonly observed phenomena [20][21][22][23][24][25][26] , although weak localization has also been demonstrated [26][27][28] , as well as anti-localization in very high purity films 29 .…”
Section: Introductionmentioning
confidence: 99%